2022
DOI: 10.1016/j.xjidi.2021.100063
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Aspects of the Association between Exposure to the World Trade Center Disaster and Risk of Cutaneous Melanoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Demonstrating the importance of long‐term follow‐up studies with adequate statistical power, our recent pooled analysis of three cohorts of WTC workers showed that greater intensity of WTC exposure was associated with an increased risk of melanoma, prostate, thyroid, and tonsil cancers 9 . Additionally, two recent analyses of melanoma and prostate cancer in WTC responders found significantly shorter latency/induction periods from time of WTC exposure to onset of illness, when compared to previous reports 10,11 . These cancers are characterized as well by disparities by race and ethnicity.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Demonstrating the importance of long‐term follow‐up studies with adequate statistical power, our recent pooled analysis of three cohorts of WTC workers showed that greater intensity of WTC exposure was associated with an increased risk of melanoma, prostate, thyroid, and tonsil cancers 9 . Additionally, two recent analyses of melanoma and prostate cancer in WTC responders found significantly shorter latency/induction periods from time of WTC exposure to onset of illness, when compared to previous reports 10,11 . These cancers are characterized as well by disparities by race and ethnicity.…”
Section: Introductionmentioning
confidence: 86%
“…9 Additionally, two recent analyses of melanoma and prostate cancer in WTC responders found significantly shorter latency/induction periods from time of WTC exposure to onset of illness, when compared to previous reports. 10,11 These cancers are characterized as well by disparities by race and ethnicity. In particular, the incidence of prostate cancer is higher in Blacks and that of melanoma and thyroid and oropharyngeal cancer is higher in Whites.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 247 incident cases of cutaneous melanoma were observed among White RRWs (the numbers of cases among non‐White RRWs were too small to analyze) 37 . No increase in the incidence of melanoma was detected during 2002 through 2004; however, beginning in 2005, a 34% increased risk was observed compared with the NYS reference population (HR, 1.34; 95% CI, 1.18‐1.52).…”
Section: Published Reports On Wtc‐rrws From the Combined Cohortmentioning
confidence: 99%